Effects of brassinolide on the physiological characteristics of maize (Zea Mays L.) Cultivars Under salt stress. - Ji, Biao; Li, Jie; Xia, Yina; Li, Zan (Bangladesh Journal of Botany, 2023)
Effects of brassinolide on the physiological characteristics of maize under salt stress were investigated. Effect of exogenous application of brassinolide on the antioxidant system, endogenous hormone levels, sodium and potassium ion contents of the plants were measured in a salt-tolerant maize cultivar, Xianyu 335, and a salt-sensitive maize cultivar, Dongnong 253. Brassinolide induced better alleviation of physiological damage in different salt-sensitive maize cultivars under salt stress treatment. Exogenous administration of brassinolide was found to increase the antioxidant enzyme activity, modulate the endogenous hormone levels, and promote potassium and sodium excretion by the plants. The effect was more significant in salt-sensitive maize cultivars. Bangladesh J. Bot. 52(2): 551-558, 2023 (June) Special